A Test Utilization Approach to the Diagnostic Workup of Isolated Eosinophilia in Otherwise Morphologically Unremarkable Bone Marrow: A Single Institutional Experience. Issue 5 (19th July 2018) - Fang, Hong; Ketterling, Rhett P; Hanson, Curtis A; Pardanani, Animesh; Kurtin, Paul J; Chen, Dong; Greipp, Patricia T; Howard, Matthew T; King, Rebecca L; Van Dyke, Daniel L; Reichard, Kaaren K
Abstract: Objectives: Determine ancillary test utilization for the workup of isolated eosinophilia in otherwise morphologically unremarkable bone marrow (BM). Methods: We evaluated BM ancillary testing performed in cases with isolated eosinophilia and otherwise morphologically unremarkable BM. Cases with abnormal morphology (eg, dysplasia, basophilia) and/or findings suggestive of a disorder (eg, unexplained thromboses, lymphoma) are specifically excluded. Results: A total of 132 cases met inclusion criteria. Ten cases had an ancillary testing abnormality that warranted a more specific hematologic diagnosis: four cases of lymphocytic variant of hypereosinophilic syndrome, three cases of myeloid neoplasm with PDGFRA rearrangement, and one case each of myeloid neoplasm with PDGFRB rearrangement, chronic eosinophilic leukemia, and morphologically occult systemic mastocytosis. No cases revealed a cryptic PDGFRB or BCR/ABL1 rearrangement or JAK2 V617F mutation. Conclusions: Findings from our institutional experience support initial testing in isolated eosinophilia with otherwise unremarkable BM to include PDGFRA rearrangement, tryptase/CD25 immunohistochemistry, cytogenetics, and T-cell flow cytometry/receptor gene rearrangement. This approach achieves diagnostic quality and test utilization efficiency in our clinical practice.